2011
DOI: 10.3109/08820139.2011.581732
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy Against Invasive Fungal Diseases in Stem Cell Transplant Recipients

Abstract: Despite the availability of new antifungal compounds, morbidity and mortality of invasive fungal disease in allogeneic hematopoietic stem cell recipients are still unacceptably high. Over the past decade, one could witness an exciting improvement of the understanding of the molecular pathogenesis and of the complexity of host antifungal immune responses. This, in turn, provides critical information to augment host immunity against fungal pathogens. Strategies for enhancing the immune system include the adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…As such, it has been implicated as a treatment option in (invasive) fungal infections [20,21]. Moreover, limited evidence suggests that recombinant IFN-γ (rIFN-γ) has a beneficial effect on the outcome of fungal infections in patients with chronic granulomatous disease (CGD) [22], HIV [23-25], leukemia [26,27], and in patients receiving organ transplants [28].…”
Section: Introductionmentioning
confidence: 99%
“…As such, it has been implicated as a treatment option in (invasive) fungal infections [20,21]. Moreover, limited evidence suggests that recombinant IFN-γ (rIFN-γ) has a beneficial effect on the outcome of fungal infections in patients with chronic granulomatous disease (CGD) [22], HIV [23-25], leukemia [26,27], and in patients receiving organ transplants [28].…”
Section: Introductionmentioning
confidence: 99%
“…There is a high degree of mortality in these cases even with treatment, highlighting the need for a better understanding of the immune response involved in controlling fungal infections in order to develop improved treatments [2], [3]. Responses to fungal infections involve both innate and adaptive immunity [4].…”
Section: Introductionmentioning
confidence: 99%
“…12 In addition, we and others have shown that also activated natural killer cells-which can be easily selected and enriched for-can mediate anti-aspergillus activity. [13][14][15] Data from our group have also demonstrated that isolated gamma-delta T cells can mediate anti-aspergillus activity. 11 Gamma-delta T lymphocytes can be highly enriched for under good manufacturing practice conditions using the Clinimacs device 16,17 and also easily be activated and expanded in vivo by stimulation with aminobisphosphonates.…”
Section: Immunotherapy For Fungal Infectionsmentioning
confidence: 96%